Communicative capacity Public encounters in participatory theory and practice - Bartels, Koen P.R (Policy Press, 2015)
Participatory democracy has become an unshakable norm and its practice is widespread. Nowadays, public professionals and citizens regularly encounter each other in participatory practice to address shared problems. But while the frequency, pace and diversity of their public encounters has increased, communicating in participatory practice remains a challenging, fragile and demanding undertaking that often runs astray. This unique book explores how citizens and public professionals communicate, why this is so difficult and what could lead to more productive conversations. Using timely, original empirical research to make a thorough comparative analysis of cases in the United Kingdom, the Netherlands and Italy it shows policy makers, practitioners, students and academics the value of communicative capacity.